Diversifikasi Teknologi Kelapa Berbasis Business Research Learning di Kecamatan Tanete Rilau Kabupaten Barru - Aslinda Aslinda; Muh. Rizal S.; Muhammad Luthfi Siraj; Syarifuddin Syarifuddin; Syamsu Alam (DEDIKASI, 2023)
Abstract. Community service activities carried out for the community, especially coconut farmers in Tanete Rilau District, Barru Regency which aim to create knowledge and skills for the community to process coconut waste products through the use of technology to produce various products that have a level of added value for economic income. The final stage is the final evaluation and reporting. This PKM activity uses a method in the form of skills training through lectures, demonstrations and question and answer and the target of this PKM activity is the coconut farming community. The results of the implementation of this PKM were attended by 19 coconut farmer participants where the results of the training activities were assessed as target achievement in terms of the aspect of material achievement that had been planned and the number and enthusiasm of participants. The achievement of the material targets that have been planned for the Community Partnership Program activities can be assessed very well. This is because all the material presented by the presenters can be understood by the participants even though from the aspect of skills both in making handicraft products from coconut waste as well as skills in using machine technology and social media platforms which are still limited. The effective solution for this PKM activity is that this training is also carried out with continuous coaching activities by farmers who can communicate directly with the PKM team at any time to continuously train farmers in managing coconut waste to produce a product that has economic value. Keywords: Diversification, Coconut Technology, Business Research